(untitled) (Revista Argentina de Cirugía, 2021)
Background:current screening methods allow to diagnose rectal lesions at earlier stage with great success regarding local resection so as to reduce the morbidity and mortality as regards radical surgery. Transanal minimally invasive surgery (TAMIS) consists in removing rectal lesions using transanal evices with usual laparoscopic instrumentation. In our country, we could not find series reports of this innovative technique. Objective: our aim was to assess the feasibility and safety of removing extra-peritoneal benign and malignant lesions of the rectum using TAMIS. Materials and methods: between February 2013 and December 2015, patients with extra-peritoneal lesions of the rectum were selected prospectively. We included: benign lesions ≥ 3 cm; neuroendocrine tumors less than 2 cm; T1N0 with no adverse histological features; patients with adenocarcinoma T2N0, with high surgical risk, or those rejecting radical surgery; patients with a complete clinical remission following neoadjuvant therapy; and those with a doubtful pathological response. Results: 16 patients underwent surgery: 5 with general anesthesia and 11 with spinal anesthesia. The average sizes of the lesions were 3.5 cm, with a medial distance of 5.8 cm from the anal margin and a mean operating time of 45.5 minutes. Surgical site was left open in 15 patients. In 15 cases unfragmented samples were taken, one with a compromised resection margin; 4 were benign lesions; one carcinoid tumor; and eleven adenocarcinomas: 1 ypT0, 3 pT1 y 6 pT2. From the latter (T2), three were substaged through MRI. There were two recurrences, 25% morbidity: one degree 1 and three degree 2